Treatment continuation of four long-acting antipsychotic medications in the Netherlands and Belgium: A retrospective database study - Decuypere, Flore; Sermon, Jan; Geerts, Paul; Denee, Tom R.; De Vos, Cedric; Malfait, Bart; Lamotte, Mark; Mulder, Cornelis L. (PLOS ONE, 2017)
Achieving greater continuation of treatment is a key element to improve treatment outcomes in schizophrenia patients. However, reported treatment continuation can differ markedly depending on the study design. In a retrospective setting, treatment continuation remains overall poor among patients using antipsychotics. This study aimed to document the difference in treatment continuation between four long-acting injectable antipsychotics based on the QuintilesIMS LRx databases, national, longitudinal, panel based prescription databases of retail pharmacies, in the Netherlands and Belgium. Paliperidone palmitate once monthly, risperidone microspheres, haloperidol decanoate, and olanzapine pamoate were studied. This study demonstrated significantly higher treatment continuation of paliperidone palmitate once monthly compared to risperidone microspheres (p-value<0,01) and haloperidol decanoate (p-value<0,01) in both countries, a significantly higher treatment continuation of paliperidone palmitate once monthly compared to olanzapine pamoate in the Netherlands (p-value<0,01), and a general trend towards better treatment continuation versus olanzapine pamoate in Belgium. Analysing the subgroup of patients without previous exposure to long-acting antipsychotic treatment revealed the positive impact of previous exposure on treatment continuation with a subsequent long acting treatment. Additionally, the probability of restarting the index therapy was higher among patients treated with paliperidone palmitate once monthly compared to patients treated with risperidone microspheres and haloperidol decanoate. The data source used and the methodology defined ensured for the first time a comparison of treatment continuation in a non-interventional study design for the four long-acting injectable antipsychotics studied.